Peran Kode Etik Profesi Kehakiman terhadap Pertanggungjawaban Hakim dalam Memutus Perkara di Pengadilan - Ryan Abdul Muhit (LEX LAGUENS: Jurnal Kajian Hukum dan Keadilan, 2023)
Ethics is a branch of philosophy that talks about human practice, or about human actions or behavior as humans. Professional ethics as a norm that regulates how members of a profession carry out their duties and functions as well as possible according to the demands of ethical, moral, and even legal values ​​and professional justice that they carry, so that they are truly professional in carrying out their professional functions. This research is a qualitative type with a library research approach, which is research with data obtained from various sources and literature. Collecting data obtained from reviewers of relevant literature and relating to this research. The results of this study are the role of the code of ethics of the judiciary on accountability in deciding cases is as a basis or guideline and is preventive in nature against the authority of judges in carrying out their duties and functions as judges. Then the code of honor of judges also adheres to the principle of submission to the law.